Climatic Niche Estimation, Trait Evolution and Species Richness in North American Carex (Cyperaceae) - Pender, Jocelyn E. (Université d'Ottawa / University of Ottawa, 2016)
With close to 2100 species, the flowering plant genus Carex (Cyperaceae; sedges) is an example of an evolutionary radiation. Despite its potential for use as a model taxon in evolutionary studies, the diversification of sedges remains largely unexplored. This thesis realizes the potential of Carex as an evolutionary model group by using it to ask questions about species richness patterns. More specifically, it seeks to determine the relationship, if any, between rates of trait evolution and species richness. This tests the hypothesis that organisms with increased abilities to evolve new traits, speciate more rapidly. Morphological and ecological (habitat and climatic niche) traits are modelled on a nearly complete regional (North America north of Mexico) phylogeny and rates of trait evolution are compared among non-nested sister groups. However, before trait evolution is modelled, this work evaluates the sensitivity of climatic niche estimates to underlying distribution datasets. It tests the agreement of niche estimates derived from the commonly used online repository GBIF (the Global Biodiversity Information Facility) and county-level distributions via BONAP (the Biota of North America Program). Results showed that in the context of phylogenetic comparative analyses, it is not vital to obtain highly accurate climatic niche estimates. The second study found significant positive correlations between the rates of climatic niche, habitat and reproductive morphological evolution and species richness. This result supports the role of high trait lability in generating species richness and more generally, the idea that high trait disparity through evolutionary time leads to species success.
Keywords: Trait evolution; Climatic niche; Species richness